Changing Varietal Distinctiveness of the World's Wine Regions: Evidence from a New Global Database*. (14th April 2014) - Anderson, Kym
Abstract Consumers are always looking for new types of wines. Producers compete for their attention by trying to product differentiate at the same time as they are responding to technological improvements, climate change, and evolving demand patterns. In doing so, wineries are increasingly highlighting their regional and varietal distinctiveness. This paper examines the extent to which the choice of winegrape varieties in wine regions has already changed over the first decade of the twenty-first century in both the Old World and New World. In doing so, it reports a varietal intensity index of different regions and an index of similarity of varietal mix between regions. The study is based on a new database of vine-bearing areas circa 2000 and 2010 for nearly 1, 300 DNA-distinct winegrape varieties, spanning over 600 regions in 44 countries that together account for 99 percent of the world's wine production. (JEL Classifications: D24, L66, Q13, Q15)